Weeping without tears: Kurdish female kolbers and gendered necropolitics of state in Iran - Mohammadpour, Ahmad; Javaheri, Aso (Gender, work, and organization, 2025)
This article disentangles the nexus between coloniality, territoriality, and gendered necropolitics of state in Iran and how it shapes the lives of the Kurdish female cross‐border laborers (kolbers, in Kurdish) in Eastern Kurdistan (Rojhelat, in Kurdish). Drawing on Achille Mbembe's notion of “necropolitics,” we conceptualize kolberi as a work of death that subjects Kurds to indiscriminate and collective punishment through necro‐disciplinary measures, exposing them constantly to precarious conditions. The necropolitics of Kurdish female kolberi underlines how the meaning of death, like the meaning of life (in biopolitics), is produced and managed through elements of embodiment―bodies, of who kills, and of who is marked for death and for taking life. We interviewed 13 Kurdish women in Rojhelat who have been involved in kolberi over the last few years. By bringing the gendered dimension of kolberi to the forefront, our article theorizes the experiences of women kolbers as occurring in a “death world”―a world where female kolbers' lives are perpetually endangered by the state apparatus of death and silenced by the patriarchal regime of “truth.” Our analysis reveals a form of state violence that highlights the gendered expression of “colonized subjects.”